Comment on “Variational Iteration Method for Fractional Calculus Using He’s Polynomials” - Ji-Huan He (Abstract and Applied Analysis)
Recently Liu applied the variational homotopy perturbation method for fractional initial boundary value problems. This note concludes that the method is a modified variational iteration method using He’s polynomials. A standard variational iteration algorithm for fractional differential equations is suggested.